2020
DOI: 10.1002/nop2.640
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and analysis of patient safety competency of Chinese nurses with associate degrees: A cross‐sectional study

Abstract: Aim To analyse the patient safety competency (PSC) of Chinese nurses with associate degrees (ADNs) and explore factors. Design A cross‐sectional study. Methods A convenience sample of 451 ADNs working in 18 hospitals located in Chongqing city of China was investigated using the Patient Safety Competency Nurse Evaluation Scale (PSCNES). Descriptive and inferential statistics were used to analyse the data. Results AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…A Chinese study showed that healthcare providers with professional titles were more likely to have an awareness of perceiving the risk of medical malpractice. 19 However, previous research showed increased emotional difficulty when there was a possibility of adverse events. 20 Thus, healthcare providers with a higher level of professional titles tend to undertake more work stress and find it more challenging to handle emotional distress, which indicates that they need support, especially after they experience PSIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Chinese study showed that healthcare providers with professional titles were more likely to have an awareness of perceiving the risk of medical malpractice. 19 However, previous research showed increased emotional difficulty when there was a possibility of adverse events. 20 Thus, healthcare providers with a higher level of professional titles tend to undertake more work stress and find it more challenging to handle emotional distress, which indicates that they need support, especially after they experience PSIs.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, the professional title is a sign that reflects healthcare providers’ working ability and technical level in China. A Chinese study showed that healthcare providers with professional titles were more likely to have an awareness of perceiving the risk of medical malpractice 19 . However, previous research showed increased emotional difficulty when there was a possibility of adverse events 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the level of nurses' patient safety competency and its affecting factors. Some studies have reported a moderate level of patient safety competency among Korean (Hwang, 2015; Jin & Yi, 2019) and Chinese nurses (Yan et al, 2020). Some variables identified as affecting patient safety competency include nurses' educational backgrounds (Kim & Han, 2016), clinical experience (Hwang, 2015; Jin & Yi, 2019; Murray et al, 2018), critical thinking disposition (an individual's motivation or attitude toward thinking critically) (Jin & Yi, 2019; Kim & Han, 2016), teamwork (Jin & Yi, 2019) and having the experience of reporting patient safety accidents (Han & Roh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A nurse must independently monitor, treat (keep a nursing history) certain groups of patients and call the doctor for consultation only. Nurses having the best knowledge can do their job more efficiently, which will not only influence the well-being of patients, improve the provision of medical care and satisfy nurses with their work [6].…”
Section: Introductionmentioning
confidence: 99%